Torsion Stiffness of a Protein Pair Determined by Magnetic Particles - Janssen, X.J.A. (The Biophysical Society, 2011)
We demonstrate the ability to measure torsion stiffness of a protein complex by applying a controlled torque on a magnetic particle. As a model system we use protein G bound to an IgG antibody. The protein pair is held between a magnetic particle and a polystyrene substrate. The angular orientation of the magnetic particle shows an oscillating behavior upon application of a rotating magnetic field. The amplitude of the oscillation increases with a decreasing surface coverage of antibodies on the substrate and with an increasing magnitude of the applied field. For decreasing antibody coverage, the torsion spring constant converges to a minimum value of 1.5 × 10(3) pN·nm/rad that corresponds to a torsion modulus of 4.5 × 10(4) pN·nm(2). This torsion stiffness is an upper limit for the molecular bond between the particle and the surface that is tentatively assigned to a single protein G–IgG protein pair. This assignment is supported by interpreting the measured stiffness with a simple mechanical model that predicts a two orders of magnitude larger stiffness for the protein G–IgG complex than values found for micrometer length dsDNA. This we understand from the structural properties of the molecules, i.e., DNA is a long and flexible chain-like molecule, whereas the antibody-antigen couple is orders of magnitude smaller and more globular in shape due to the folding of the molecules.